Comparison of Pterygium Recurrence Rate between Consultants and Residents ? 219 using 5 FU as an Adjuvant after excision of Primary Pterygium - Gbadegesin Oluwatosin G, Ubah Josephine N (Pakistan Journal of Ophthalmology, 2018)
Purpose: To compare the recurrence rates of pterygium between consultants and residents after primary pterygium excision. Material and Methods: A retrospective study of the primary pterygium excision cases with intraoperative 5-FU as an adjuvant therapy, done in a tertiary institution was carried out. All 36 case notes retrieved were reviewed. Results: Residents operated on 16 patients while consultants operated on 20 cases. Of the 16 operations done by residents, 6(37.5%) had recurrence while it was seen in4 (20%) of the cases performed by consultants. The difference in recurrence not statistically significant. P=0.244. Conclusion: Although there was no statistical difference between the two groups considered in this study, the recurrence rate is still higher among the residents.